Can We Avoid the Repugnant Conclusion?. (22nd April 2016) - Parfit, Derek
Abstract : According to the Repugnant Conclusion : Compared with the existence of many people who would all have some very high quality of life, there is some much larger number of people whose existence would be better, even though these people would all have lives that were barely worth living. I suggest some ways in which we might be able to avoid this conclusion. I try to defend a strong form of lexical superiority.